2019
DOI: 10.1016/j.jns.2018.12.020
|View full text |Cite
|
Sign up to set email alerts
|

The King-Devick test in an outpatient concussion clinic: Assessing the diagnostic and prognostic value of a vision test in conjunction with exercise testing among acutely concussed adolescents

Abstract: Objective-This study investigated the diagnostic and prognostic value of the King-Devick (K-D) test in conjunction with treadmill testing in adolescents after sport-related concussion (SRC) in an outpatient concussion management clinic without baseline measures. Design-Prospective cohort.Methods-The K-D test was administered pre-and post-exercise on a graded treadmill test to acutely concussed (AC, <10 days from injury, n=46, 15.4±2.1 years) participants for 2 clinic visits (1 week apart) and to matched contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…This study validates a previous finding 6 that participants who did not exhibit the typical improvement in KD test time after exertion took longer to recover from SRC than those whose postexertion time improved. In addition, participants who did not show the typical improvement reported more symptoms on the initial-visit PCSS, which was significantly associated with recovery.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This study validates a previous finding 6 that participants who did not exhibit the typical improvement in KD test time after exertion took longer to recover from SRC than those whose postexertion time improved. In addition, participants who did not show the typical improvement reported more symptoms on the initial-visit PCSS, which was significantly associated with recovery.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, a previous study 6 demonstrated a mean reduction of 3.2 seconds in KD test time in healthy control individuals tested 1 week apart at rest (P , .001). The authors of 2 studies 6,25 have assessed the effect of systematic exercise on the KD test in healthy controls. Lawrence et al 6 found a mean reduction of 2.3 seconds (P , 0.001) after the BCTT, and Eddy et al 25 described a mean reduction of 1.7 seconds after a bout of moderate exertion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors estimated that for every 1-point of worsening of overall SAC score, there was a 4.7-s increase in K-D total time score from baseline ( p =0.001), while every 1-point worsening of BESS had an estimated 1.6-point increase in K-D time score from baseline ( p =0.043). Lawrence and colleagues studied the diagnostic and prognostic value of the K-D test in an outpatient setting 20. They administered the K-D test pre- and post-treadmill test to both individuals who had a concussion recently (n=46) and matched controls (n=30) 20.…”
Section: Reliability Validity and Normative Datamentioning
confidence: 99%